Electronic Alarm Uses Arduino with Ultrasonic Sensor and MP3 Module as the School Bell Time at Kemala Bhayangkari Delog Vocational School: Electronic Alarm Uses Arduino with Ultrasonic Sensor and MP3 Module as the School Bell Time at Kemala Bhayangkari Delog Vocational School - Daud Iswandii; Agung Triayudi; Endah Tri Esti Handayani (Jurnal Mantik, 2020)
School bell is a device that is needed at school as a supporting medium to convey information or as notification of changing of hours to students and teachers. But the problem that often arises is that the sound of the bell produced is generally only limited to the sound of the buzzer that has no specific information and is difficult to understand, besides the bell is activated manually through the picket staff whose job is to convey information and ring the school bell at certain hours or times. The ARDUINO-based automatic school bell application is equipped with a mini DFPlayer module that is able to play the .MP3 sound file format, so information conveyed through the bell can be in English and Indonesian[10]. With the ability to play sound files in .MP3 formats, the information conveyed through the bell can be easily understood by all stakeholders in the school.